Isolation and molecular characterisation of Malassezia pachydermatis from dogs in Kerala - S. Abhijith; Chintu Ravishankar; R. Rajasekhar; K. Sumod; P. Vinu David; P. Habeeb Biju; C. Harish; A. Javed Jameel; K. Daniel Anju; Suprativ Sarma; P. Vishnu; K. Sandhiya (Journal of Veterinary and Animal Sciences)
Malassezia spp. are commensals of the normal cutaneous microbiota of animals that may become opportunistic pathogens under certain conditions and cause dermatitis and otitis externa in dogs. In the present study, a total of 47 dogs with clinical signs of pruritus, alopecia, scaly skin, erythema, foul odour, ear affections, hyperpigmentation and lichenification were found to be positive for budding yeast cells on cytological examination of clinical samples. These samples were subjected to culture on Modified Dixon agar (MDA), for the isolation of Malassezia spp. and the organism was isolated from eight cases. The identity of the isolates was confirmed as M. pachydermatis by polymerase chain reaction (PCR) targeting the LSU rRNA of Malassezia spp. followed by sequencing. Molecular characterisation of the isolates based on LSU rRNA region revealed that two types of M. pachydermatis isolates are prevalent among dogs in Kerala.